The Design and Performance Evaluation of a Wireless Sensor Network Based Irrigation System on Different Soil Types - Buhari Umar; Eustace Manayi Dogo; Bello Kontagora Nuhu; Arifa Khatoon Haq; Paul Tobi Olaleye (Journal of Digital Food, Energy & Water Systems)
In the Nigerian economy, agriculture plays a very important role, and most of its people depend on it for their livelihood. Agricultural practices in the country are still mainly based on conventional, traditional methods of farming which usually results in wastage of water resources and low production of crops to meet the country's demand. There is a need to transform farming from the traditional way to a more efficient method with optimum water utilization. Irrigation is an assistive measure to salvage the problem of inadequate water for dry season farming. Irrigation consumes a lot of water, time and must be done on a timely basis. The automated irrigation system helps to curb the problem of overwatering and under watering of the land. This research proposed an Arduino-based smart irrigation system using a wireless sensor network to overcome the problem of overwatering, underwatering, and efficient time utilization in farming. The system is implemented using Arduino IDE, Proteus Simulation Tools, and Blynk Platform. The effect of the four-mobile network: MTN, GLO, Airtel and 9mobile on response time for Gidan- Kwano area was evaluated. Testing carried out on the system resulted in a response time of 0.75 seconds for Glo 2G network and 0.45 seconds for Glo 4G network. Less than 1sec in the worst-case scenario. This makes the system effective in terms of time response, thereby eradicate the waste of time that manual system operation poised to irrigation scheduling. Also, the appropriate soil moisture content is maintained, whether it rains or not. This reduces excesses and ensures healthy plant growth, increasing agricultural productivity, and cultivating crops are made possible throughout the year. The system also will help in driving agricultural innovation through the use of IoT.